Development of the Culture-Based Batik Trusmi Industrial Zone - Ronan Afrizal Hadi; Khaerudin Imawan; Leni Rohida (Apollo: Journal of Tourism and Business, 2026)
Batik Trusmi Industrial Area is a culture-based creative economy center in Cirebon Regency which is not only known as a producer but also as a cultural tourism destination. The purpose of this study is to explain the role of culture-based tourism communication in conservation and development in the Batik Trusmi Area, as well as identifying obstacles in developing the area in relation to its conservation and the role of the local communities and tourists in sustaining the area. In order to achieve this objective, the author utilizes a qualitative research design with the descriptive approach which includes in-depth interviews, observations, and documentation among batik artisans, managers of batik shops, tourists, and micro, small, and medium enterprises (MSMEs). The findings reveal that culture-based tourism communication plays an essential role in the delivery of the values, meanings, and philosophy of batik to tourists via direct communication and culture education. Nevertheless, there are some obstacles in developing the area such as artisan regeneration, printed batik competition, and the lack of supporting facilities. The involvement of the local communities and tourists play important roles in building the area identity as a sustainable cultural tourism destination.